PENURUNAN SKALA NYERI PENGGUNAAN KETOROLAK INJEKSI PADA PASIEN OPERASI SESAR DI RUMAH SAKIT ROEMANI MUHAMMADIYAH SEMARANG - Octasari, Paulina Maya; Inawati, Menik (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2021)
Pain management after cesarean section must be done properly to prevent the emergence of chronic pain in patients. Ketorolac is the first choice as an analgesic to treat that pain. The appropriate dosage and time of analgesic treatment have impact to pain scale decreasing and another analgesic adding. The purpose of this study was to determine the magnitude of the reduction in the pain scale of using ketorolac injection in cesarean section patients at Roemani Muhammadiyah Semarang Hospital. This research is a descriptive observational study. The research design is cross-sectional study by using retrospective data. The data were taken through the medical records of patients with cesarean section at Roemani Muhammadiyah Hospital Semarang for the period July - December 2019. The sample of this study was elective caesarean section patients who received ketorolac injection therapy in that period. The age range of patients taken was 18- 45 years. The reduction in pain scale was measured by the Numeric Rating Scale (NRS) method. The results showed that the sample data obtained and those who met the inclusion criteria were 88 patients. Before the administration of ketorolac injection, the number of patients with moderate pain was in the greatest number, namely 53.41% and after the administration of ketorolac injection, the number of patients with mild pain was the greatest, namely 63.64%. Patients who experienced a decrease in the pain scale of 39.78%, the stability of the pain scale of 47.72%, and an increase in the pain scale of 12.50%. The average reduction in the pain scale of cesarean patients who received ketorolac injection at the Roemani Muhammadiyah Semarang Hospital was 1.09. Keywords: Cesarean section, Pain, Pain scale, Ketorolac, Roemani Muhammadiyah Hospital Semarang.